Occupational physical demands and hip osteoarthritis. - Cvijetić, S; Dekanić-Ozegović, D; Campbell, L; Cooper, C; Potocki, K (1999)
The authors investigated the influence of physical strain at work on radiological signs of hip osteoarthritis. The study included 295 men and 298 women aged over 45 from an urban area who were classified in four groups according to physical demands of their occupation. The evaluation included clinical and radiological signs of hip osteoarthritis. The association between hip osteoarthritis and occupation was analysed using logistic regression. Though not significantly, radiological signs of hip osteoarthritis were common in subjects who worked in a standing position (odds 1.45 for men, 1.50 for women). Clinical signs of osteoarthritis in women were significantly associated with performance in a standing position (odds 3.00), whereas in men the association was more significant for jobs with high physical strain (odds 2.19). There was a sustained trend toward an increase in health risk with years of work in all job categories. Occupation did not appear to influence the development of radiological hiposteoarthritis, but the authors did establish association between clinical signs of hip osteoarthritis and work.